Nurses-led Intervention of Secondary Prevention in Patients with Acute Coronary Syndrome (ACS): A Scoping Review - Putri, Azalia Melati; Trisyani, Yanny; Megatami, Noviani; Armansyah, Nuraulia Aghnia; Ratnasari, Nia; Rahayu, Fitriani; Nurilhami, Ilham Taufik; Azizah, Neng Zihan Nurul; Nurinsani, Dwi Murti; Rahmah, Tsabitah; Widyadhari, Elysia (JENDELA NURSING JOURNAL, 2024)
Background: acute Coronary Syndrome patients often return to the hospital due to relapses that occur after they are declared cured. Secondary prevention programs are an important part for ACS patients to treat and stop the disease process and prevent them from complications and disability. Nurses have an important role in carrying out secondary prevention, especially for ACS patients to train patients to live a healthy lifestyle.Purpose: the purpose of this review study was to map and explore the implementation of secondary prevention in acute coronary syndrome patients initiated or coordinated by nurses.Methods: this study used scoping review design by including all full-text primary studies written in English and published in the last 10 years from 7 sources including EBSCO-hosted Academic Search Complete, PubMed, ScienceDirect, Sage Journals, Taylor and Francis, ProQuest, and Google Scholar. All study results were extracted manually using the tabulation method and analyzed thematically.Results: nurses can support secondary prevention through LDL reduction and lifestyle modifications. LDL reduction involves lipid-lowering medications, the NAILED-ACS approach, and Nursing Coordinated Care (NCC). Lifestyle modifications include promoting healthy habits, ensuring medication adherence, counseling for smoking cessation, and implementing programs for weight loss and physical activity.Conclusion: secondary prevention initiated or coordinated by nurses in the form of LDL reduction intervention and lifestyle modification program have been shown to be effective in reducing the risk of recurrent ischemia in patients with acute coronary syndrome.